2016
DOI: 10.1007/s10509-016-2886-x
|View full text |Cite
|
Sign up to set email alerts
|

The triple system AT Mic AB + AU Mic in the β $\beta $ Pictoris association

Abstract: Equal-mass stars in young open clusters and loose associations exhibit a wide spread of rotation periods, which likely originates from differences in the initial rotation periods and in the primordial disc lifetimes. We want to explore if the gravitational effects by nearby companions may play an additional role in producing the observed rotation period spread, as well as, the role that magnetic activity may also play. We measure the photometric rotation periods of components of multiple stellar systems and lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…-HIP 102141AB (AT Mic) The most recent photometric analysis of this system is presented by Messina et al (2016a). Our analysis of the first season of SuperWASP data, allowed us to measure the stellar rotation periods of both components.…”
Section: -2mass J20013718-3313139mentioning
confidence: 99%
See 1 more Smart Citation
“…-HIP 102141AB (AT Mic) The most recent photometric analysis of this system is presented by Messina et al (2016a). Our analysis of the first season of SuperWASP data, allowed us to measure the stellar rotation periods of both components.…”
Section: -2mass J20013718-3313139mentioning
confidence: 99%
“…Torres et al (2006) reported v sin i A = 10.1 km s −1 and v sin i B = 15.8 km s −1 for the components A and B, respectively; whereas Scholz et al (2007) determined v sin i A = 10.56 km s −1 and v sin i B = 17 km s −1 . The most recent photometric analysis of this system is presented by Messina et al (2016b). Our analysis of the first season of SuperWASP data, allowed us to measure the stellar rotation periods of both components.…”
Section: -Hip 88399mentioning
confidence: 99%
“…AT Mic (AKA GJ 799 , HD 196982, HIP 102141, CD-32 16135, 2MASS J20415111-3226073) is a literature close binary system and is highly likely to be a distant companion to AU Mic (Adams et al 1927;Caballero 2009;Shaya & Olling 2011;Messina et al 2016) with an on-sky separation of 0.23 pc which equates to 47,000 au on the sky. The AT Mic AB binary have Gaia G magnitudes of 9.576±0.003 and 9.605±0.003 respectively, so the stars are of a similar brightness and type.…”
Section: At Mic Abmentioning
confidence: 99%
“…AT Mic is believed to be a member of the β Pictoris association, with an age of ∼25 Myr (Messina et al 2017). The rotation periods of components A and B are 1.19 and 0.78 days, respectively (Messina et al 2016(Messina et al , 2017; the bolometric luminosities of components A and B have been estimated as 1.3 × 10 32 and 1.2 × 10 32 erg s −1 (0.034 and 0.031 L ☉ ), respectively (Messina et al 2017). Both components are known to be magnetically active (e.g., Gershberg et al 1999).…”
Section: Targetmentioning
confidence: 99%
“…Identifying the flaring and non-flaring (quiescent) time intervals in our observations is not straightforward, because of the above mentioned gaps in the light curves, and also because of a high activity level: AT Mic spends ∼25% of the time in a flaring state, according to Messina et al (2016), or even more than 50% of time, according to Kunkel (1970). We determined the quiescent background levels by iteratively fitting the light curves with linear functions and removing the data points that exceeded these fits by more than 1σ; this procedure effectively provides a linear fit to the lower envelope of a light curve.…”
Section: Light Curves: Overviewmentioning
confidence: 99%